2018
DOI: 10.1016/j.ijhcs.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Teaching digital literacy skills to the elderly using a social network with linear navigation: A case study in a rural area

Abstract: Information and Communication Technologies (ICTs) have considerably increased the information and communication channels, favoring the emergence of new models for relations, such as social networks. However, for elderly users whose learning has traditionally been based on linear models of information such as textbooks, unfamiliarity with Internet can be a barrier. Moreover, elderly people living in rural communities face a lack of telecommunication infrastructures, which increases their difficulties in accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 44 publications
3
91
1
3
Order By: Relevance
“…A few PWDs who were not familiar with tablets or smartphones were very unsecure when approaching the tablet and app. Preliminary studies showed [39] that the use of touchscreen technologies was frequent also in PWD but that the use of specific apps or software to support memory was reduced in PWD and caregivers and they face age barriers for the use of these apps. However, the majority think that the use of smartphones or tablets is helpful for memory and this highlights the presence of a gap between the perceived potential and the actual use of these technologies.…”
Section: Discussionmentioning
confidence: 99%
“…A few PWDs who were not familiar with tablets or smartphones were very unsecure when approaching the tablet and app. Preliminary studies showed [39] that the use of touchscreen technologies was frequent also in PWD but that the use of specific apps or software to support memory was reduced in PWD and caregivers and they face age barriers for the use of these apps. However, the majority think that the use of smartphones or tablets is helpful for memory and this highlights the presence of a gap between the perceived potential and the actual use of these technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Although technology is increasingly present in everyday life, the elderly usually face usability problems related to the unsuitable design of central features, such as the graphic user interface design and input device choices, to name some examples. On usability tests, elderly users face a greater number of usability problems than young users [ 29 , 30 , 31 ], and their ICT experience differs not only in terms of their success rate, but also in terms of emotional factors that should be included as an important part of their experience [ 32 , 33 , 34 , 35 ]. Often these negative experiences of older users are consolidated into what has been called a technophobia, that is a computer avoidance due to fear or phobia of interacting with computers [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In which order should I do the required steps?). As a consequence of the previous and the lack of ICT experience, elderly users show better performance on systems with linear navigation [ 32 , 46 , 47 ]. Another aspect that adds up to the complexity of usability in the elderly lies in the fact that the characteristics of elderly users are not static and vary over time because there are changes due to age-related decline [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the interesting topics discussed in recently published papers on the use of ICT in rural areas in the EU there is the digital literacy of older rural community representatives using a social network with linear navigation (Castilla et al, 2018). Cavicchi et al presented a case of an international student competition which aim was to actively promote one of the Italian regions (Fermo, Marche region) via social media (Cavicchi et al, 2018).…”
Section: Use Of Ict In Rural Areas (Literature Review)mentioning
confidence: 99%